The IGF/Insulin-IGFBP Axis in Corneal Development, Wound Healing, and Disease - Stuard, Whitney L.; Titone, Rossella; Robertson, Danielle M. (Frontiers in Endocrinology, 2020)
The insulin-like growth factor (IGF) family plays key roles in growth and development. In the cornea, IGF family members have been implicated in proliferation, differentiation, and migration, critical events that maintain a smooth refracting surface that is essential for vision. The IGF family is composed of multiple ligands, receptors, and ligand binding proteins. Expression of IGF type 1 receptor (IGF-1R), IGF type 2 receptor (IGF-2R), and insulin receptor (INSR) in the cornea has been well characterized, including the presence of the IGF-1R and INSR hybrid (Hybrid-R) in the corneal epithelium. Recent data also indicates that each of these receptors display unique intracellular localization. Thus, in addition to canonical ligand binding at the plasma membrane and the initiation of downstream signaling cascades, IGF-1R, INSR, and Hybrid-R also function to regulate mitochondrial stability and nuclear gene expression. IGF-1 and IGF-2, two of three principal ligands, are polypeptide growth factors that function in all cellular layers of the cornea. Unlike IGF-1 and IGF-2, the hormone insulin plays a unique role in the cornea, different from many other tissues in the body. In the corneal epithelium, insulin is not required for glucose uptake, due to constitutive activation of the glucose transporter, GLUT1. However, insulin is needed for the regulation of metabolism, circadian rhythm, autophagy, proliferation, and migration after wounding. There is conflicting evidence regarding expression of the six IGF-binding proteins (IGFBPs), which function primarily to sequester IGF ligands. Within the cornea, IGFBP-2 and IGFBP-3 have identified roles in tissue homeostasis. While IGFBP-3 regulates growth control and intracellular receptor localization in the corneal epithelium, both IGFBP-2 and IGFBP-3 function in corneal fibroblast differentiation and myofibroblast proliferation, key events in stromal wound healing. IGFBP-2 has also been linked to cellular overgrowth in pterygium. There is a clear role for IGF family members in regulating tissue homeostasis in the cornea. This review summarizes what is known regarding the function of IGF and related proteins in corneal development, during wound healing, and in the pathophysiology of disease. Finally, we highlight key areas of research that are in need of future study.